Problem Based Learning Model: How Can This Model Improve Students' Learning Motivation in Qur'an Hadith Subjects? - Saifullah; Fitri, Leni Mulia (MADINA : Journal of Islamic Studies, 2024)
Student-centered learning will create meaningful learning for each student. Student activity in learning is one of the keys to achieving learning objectives. This study aims to improve student activity in Islamic education learning by implementing the Problem based learning model. This study is a classroom action research. The subjects of this study were eighth grade students of MTs Nagari Binjai. Data were collected using observation and questionnaire techniques. Furthermore, the data were analyzed using descriptive statistical techniques. The results of the study indicate that the problem based learning model can improve student learning activity. Therefore, the problem based learning model can be used as an alternative to improve student activity in learning.